Remote sensing methods for water quality analysis in Avachа bay - A. I. Korolkova; А. A. Ivanov (Известия высших учебных заведений: Геология и разведка, 2025)
Background. Assessment of the spatial distribution of suspended matter is an essential task in monitoring the ecological state of marine waters. Excessive contents of organic particles, minerals, and fine suspended matter may have a negative impact on ecosystems, reducing water clarity and thereby deteriorating the conditions necessary for photosynthesis. Aim. To assess the sea water turbidity and the spatial distribution of suspended matter in the coastal part of the Avacha Bay using remote sensing methods. Materials and methods. Remote sensing methods are widely used to monitor the state of marine environments through various parameters, such as water turbidity, chlorophyll content, surface water temperature, etc. Modern satellite systems, e.g., Sentinel-2, provide multispectral images for further calculation of spectral indices. In this work, water turbidity was assessed using the normalized difference turbidity index (NDTI). Results. The areas of increased turbidity are formed due to not only anthropogenic impact, but   also the geological structure of the environment. The Avacha Bay is a zone under the influence of the Avacha-Koryaksky and other groups of volcanoes. In the spring and summer periods, during active melting of snow and rain precipitation, an intensified flow of the Avacha and Paratunka rivers carrying waterborne volcanic products increases the content of suspended solids in the water. The spatial distribution of NDTI was analyzed, and the maps of water turbidity were compiled. Conclusion. The constructed maps of the spatial distribution of the NDTI index for a number of years showed that the delta of the Avacha and Paratunka rivers, as well as the coastal parts of the Avacha Bay, are associated with increased water turbidity.